The Development of Morphological Knowledge and Spelling in French - Mussar, Ruth; Sénéchal, Monique; Rey, Véronique (Frontiers in Psychology, 2020)
The French orthographic system is particularly difficult to learn because nearly 30% of words in the lexicon end with a silent letter. One metalinguistic skill that has been identified to facilitate spelling acquisition in French is morphological knowledge. This cross-sectional study investigated the construct of morphological knowledge, its development, and its role in building accurate orthographic representations in a sample of francophone elementary students. We proposed that morphological knowledge, a superordinate process, encompasses children’s implicit use of morphemes in everyday language and their conscious, targeted manipulation of morphemes. In the present study, we assessed children’s recognition of morphogrammes, the silent letter endings (SLEs) of root words that become pronounced in suffixed forms (e.g. the silent t in chant /ʃã/ [song]→ chanteur /ʃãtœʀ/ [singer]). When spelling root words, children may mark morphogrammes by recalling morphologically related words in which the morphogramme is not silent—thus, morphological knowledge was hypothesized to positively predict morphogramme spelling. 123 children in grades 1 to 3 were assessed on four measures of morphological knowledge, two measures of spelling recognition; and a dictation of pseudowords to explore their inclusion of silent-letter endings in novel words. As expected, morphological tasks that required explicit morphological manipulations were harder than implicit ones. Moreover, first graders struggled to complete explicit morphological tasks, while third graders were near ceiling performance on implicit tasks. Nevertheless, the four tasks converged on a single morphological knowledge construct as confirmed by a factor analysis. Importantly, morphological knowledge explained unique variance in children’s accurate representation of silent letter endings after controlling for grade, reading for pleasure, and general orthographic recognition of words. Finally, children rarely used silent-letter endings when spelling pseudowords; however, when they did, they displayed sensitivity to the appropriate phonological context for the letter used. The findings are in accord with theoretical models suggesting that the representations of letters without phonological value are difficult to construct, and may remain fuzzy.